Providers' Perceptions Of The Factors Influencing The Implementation Of The New York State Mandatory HIV Testing Law In Two Urban Academic Emergency Departments - Schnall, Rebecca (2013)
OBJECTIVES: Of the 1.1 million people in the United States infected with human immunodeficiency virus (HIV), more than 20% are unaware of their infection. To increase early diagnosis and treatment, New York State recently passed legislation mandating that HIV testing be offered to all patients, ages 13 to 64 years, receiving health care services. Implementation of this legislation is complex, especially in the emergency department (ED). This study explores ED providers' perceptions of the factors affecting the implementation of the law. METHODS: The authors conducted six focus group sessions and three in-depth interviews with ED health care providers from two New York City teaching hospitals. Sessions were audiotaped and transcribed. Data were coded and summarized thematically through an iterative process after each session. RESULTS: A total of 49 providers participated and data saturation was achieved. Six factors were identified that predispose a provider to offer an HIV test: 1) self-efficacy, 2) behavioral intention, 3) the testing process, 4) provider knowledge of the legislation, 5) type of HIV test, and 6) follow-up procedures. Five factors were identified that enable providers to offer an HIV test: 1) resources related to time, 2) space, 3) staff, 4) type of test, and 5) timing of the offer. Improving access to HIV testing, linkage to care, and public health were all key factors in reinforcing providers' desire to offer HIV tests. Concerns regarding overall cost saving and coverage for the test were indicated as barriers that needed to be resolved in order to reinforce the providers to offer an HIV test. CONCLUSIONS: Understanding the factors influencing the practice of ED providers charged with carrying out this mandate is critical. Despite earlier research that indicated that offering HIV testing to ED patients is largely influenced by cost, this study found additional factors that are important to consider to effectively implementing HIV testing in the ED.